Open field study on the efficacy of oral fluralaner for long-term control of flea allergy dermatitis in client-owned dogs in Ile-de-France region. Issue 1 (December 2016) - Crosaz, Odile; Chapelle, Elodie; Cochet-Faivre, Noëlle; Ka, Diane; Hubinois, Céline; Guillot, Jacques
Abstract Background Fluralaner is the first orally administered isoxazoline to provide 12 weeks of activity against fleas and ticks after a single administration. As a result of its potent anti-flea activity, oral fluralaner may be proposed as a component of a strategy for the control of flea allergy dermatitis (FAD) in dogs. The open field study reported here assessed the efficacy of fluralaner for long-term control (up to 6 months) of FAD in affected client-owned dogs maintained under common household conditions in the Ile-de-France region. Methods This was an open pre-treatment versus post-treatment study. Client-owned dogs with clinical signs of FAD were recruited and treated with oral fluralaner (Bravecto®) at 25-56 mg/kg body weight on days 0 and 84. The dogs' condition was assessed at each visit (on days 0, 28, 84 and 168) using the following three parameters: (i) extent of skin lesions based on the scoring system for canine FAD; (ii) pruritus severity based on the pruritus visual analog scale; (iii) presence or absence of fleas or flea feces. Results Of the 26 dogs initially enrolled, 23 were presented on day 28, 20 on day 84 and 16 for the final evaluation on day 168. Eighteen out of 20 dogs (90 %) presented on day 84 and 15 out of 16 dogs (94 %) presented on day 168 showed a complete clinical resolution. The post-treatment FAD clinical scores on days 28, 84 and 168 were significantly different from that of the pre-treatment with a reduction of 89.8 %, 98.8 % and 99.8 %, respectively. The post-treatment pruritus index values on days 28, 84 and 168 were significantly different from that of the pre-treatment with a reduction of 45.2 %, 71.2 % and 80.8 %, respectively. Conclusions The present study confirmed that oral fluralaner treatment should be considered as effective for long-term control of clinical signs in FAD affected dogs.